Pengaruh Kesadaran dan Partisipasi Mahasiswa Universitas Tidar dalam Kegiatan Pelestarian Lingkungan Kampus - Vika Indira Septiani; Farikhatul Maftukhah; Nabilla Ayudya Larasati; Oktavia Ramadhani; Tiorizal Maulana; Joko Tri Nugraha (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study aims to examine the relationship between environmental awareness and the participation of Tidar University students in supporting campus environmental conservation. The research employed a quantitative approach with an associative design and involved proportionally selected respondents from five faculties. The results indicate that students’ level of environmental awareness positively influences their participation in environmental conservation activities such as waste management and campus greening. Most respondents demonstrate an understanding of the limitations of natural resources and the importance of maintaining ecological balance, as well as a strong commitment through real actions toward environmental preservation. These findings highlight the importance of fostering ecological awareness as a foundation for enhancing student involvement in achieving a green and sustainable campus